Effect of piston bowl geometry and compression ratio on in-cylinder combustion and engine performance in a gasoline direct-injection compression ignition engine under different injection conditions. (15th December 2020) - Xu, Leilei; Bai, Xue-Song; Li, Yaopeng; Treacy, Mark; Li, Changle; Tunestål, Per; Tunér, Martin; Lu, Xingcai
Abstract: Low temperature combustion (LTC) of high-octane number fuels in compression ignition engines offers an opportunity to simultaneously achieve high engine thermal efficiency and low emissions of NO x and particulate matter without using expensive after-treatment technologies. LTC engines are known to be sensitive to the operation conditions and combustor geometry. It is important to understand the fundamental flow and combustion physics in order to develop the technology further for commercial application. A joint numerical and experimental investigation was conducted in a heavy-duty compression ignition engine using a primary reference fuel with an octane number of 81 to investigate the effects of injection timing, piston geometry, and compression ratio (CR) on the fuel/air mixing and combustion covering different regimes of LTC engines, homogeneous charge compression ignition (HCCI), partially premixed combustion (PPC), and the transition regime from HCCI to PPC. The results show that with the same combustion timing, a higher CR leads to a lower NO x, but a higher emission of UHC and CO. The piston geometry shows a significant impact on the combustion and emission process in the transition regime while it has minor influence in the HCCI and PPC regimes. It is found that high engine efficiency and low emissions of NO x, CO and UHC can be achieved in the earlier PPC regime and later transition regime. The fundamental reason behind this is the stratification of the mixture in composition, temperature and reactivity, which is dictated by the interaction between the spray and the cylinder/piston walls. Highlights: Engine performance with different SOI, compression ratio, piston geometry is studied. Three regimes (homogeneous charge compression ignition, partially premixed combustion and transition) during the SOI variation are investigated. Piston bowl shows significant impact on the charge stratification in transition regime. Compression ratio shows a tradeoff of NOx reduction with unburned hydrocarbons and carbon monoxide emissions. Optimal SOI window range from -50 to -42 o CA with the stepped-lip piston is found.